Associations of active transportation between childhood and adulthood (CADET) - Winslow, Daniel R. (Kansas State University, 2020)
Insufficient physical activity (PA) is a growing issue throughout the world. Diabetes, chronic heart disease, and shortened life expectancy are among the comorbidities resulting from insufficient PA. Studies on the development of PA behaviors have highlighted parental and environmental influences as contributors that persist across the lifespan. Active transportation (AT) is one possible avenue for PA promotion. AT is any movement from place to place without the use of a motor for occupational, utilitarian and recreational trips. The purpose of this study was to examine factors of AT development across the lifespan, including parental influence variables, which included parental support and role-modeling for AT and neighborhood environment quality associations with child AT, as well as the associations between child AT and adult AT. Positive associations were hypothesized between the following variables: parental support and child AT, parental role-modeling and child AT, child neighborhood environment and child AT, as well as child AT and adult AT. The cross-sectional survey was completed by participants (n = 98, predominately college-educated (93%), young (avg: 26±9.9 years), white (84%), females (72%) by providing recall data on their childhood (<18 years) AT behaviors, frequencies and destinations, as well as parental and environmental influences on AT. Respondents reported their current AT behaviors, frequencies and destinations, their current moderate-to-vigorous PA, and demographic information. The association between parental influence and child biking was significant (OR = 0.13, P = 0.02, 95% C.I. = 0.02, 0.75), as well as the associations between child walking and adult walking (OR = 17.61, p = 0.01, 95% C.I. = 2.01, 154.05) child biking and adult biking (OR = 11.75, p = 0.001, 95% C.I. = 2.38, 58.07), and child public transportation and adult transportation (OR = 6.92, p = 0.01, 95% C.I. = 1.79, 26.82). Findings suggested a more complex relationship between parental support behaviors and child AT than initially hypothesized and supported the hypothesized association between child AT and adult AT. The association of child AT behavior with adult AT behavior in specific AT sub-modes (walking, biking and public transportation) were supported.
Keywords: Physical activity tracking over time; Active transportation behavior; Parental influence on physical activity; Neighborhood environment for physical activity; Active transportation over time; Active transportation recall